Pengaruh Disiplin Kerja, Kepuasan Kerja, dan Motivasi Terhadap Kinerja Karyawan Billman Pada PT. PLN Electricity Services ULP Kediri Kota - Niken Budi Windiantika; Trisnia Widuri; Kukuh Harianto (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study aims to analyze the influence of work discipline, job satisfaction, and motivation on the performance of billman employees at PT. PLN Electricity Services ULP Kediri City. Employee performance plays a strategic role in ensuring the company’s service quality and operational sustainability, particularly in the field of billing services which directly impacts customer satisfaction and company revenue. The research employs a quantitative approach with a multiple linear regression method to assess both partial and simultaneous effects of the independent variables. The population of this study consisted of all 33 billman employees of PT. PLN Electricity Services ULP Kediri City, and due to the small size, a saturated sampling technique was used so that the entire population served as respondents. Primary data were collected through questionnaires distributed to all employees and then analyzed statistically. The findings indicate that, partially, work discipline has a negative and insignificant effect on employee performance, suggesting that discipline alone does not guarantee productivity improvement. On the other hand, job satisfaction and motivation both have a positive and significant effect on employee performance, showing that intrinsic and psychological factors contribute more strongly to optimal work outcomes. Furthermore, when tested simultaneously, work discipline, job satisfaction, and motivation collectively exert a positive and significant influence on employee performance. The coefficient of determination (R²) of 0.786 indicates that 78.6% of variations in performance can be explained by the three variables, while the remaining 21.4% is influenced by other factors outside this research model. These findings emphasize the importance of fostering job satisfaction and motivation through supportive management policies to enhance employee contributions and organizational effectiveness.